2021
DOI: 10.1021/acsomega.1c00185
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Extracellular Polymeric Substances from Enterobacter sp. and Their Pb2+ Adsorption Behaviors

Abstract: The objective of this study was to investigate the effects of the cultivation time, temperature, and pH value on the yield and composition of extracellular polymeric substances (EPS) from Enterobacter sp. FM-1 (FM-1) and to analyze the Pb 2+ adsorption behavior of soluble EPS (S-EPS), loosely bound EPS (LB-EPS), and tightly bound EPS (TB-EPS). Maximum EPS production was obtained when the cultivation time, temperature, and pH value were 24 h, 30 °C, and 8.0, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…LB-EPS and TB-EPS show a different composition and functionalities. As reported by Li et al (2020), LB-EPS show the highest Pb(II) adsorption abilities in comparison to TB-EPS and SB-EPS (soluble EPS) [9]. The role of LB-EPS seems to be more important in response to adverse environmental changes than the role of other EPS fractions; hence, they serve a protection function in algal metabolism [10].…”
Section: Characteristics Of Extracellular Polymeric Substancesmentioning
confidence: 74%
“…LB-EPS and TB-EPS show a different composition and functionalities. As reported by Li et al (2020), LB-EPS show the highest Pb(II) adsorption abilities in comparison to TB-EPS and SB-EPS (soluble EPS) [9]. The role of LB-EPS seems to be more important in response to adverse environmental changes than the role of other EPS fractions; hence, they serve a protection function in algal metabolism [10].…”
Section: Characteristics Of Extracellular Polymeric Substancesmentioning
confidence: 74%
“…Several studies have demonstrated that changes in the operational parameters (pH, temperature, toxic compounds, etc.) might affect the yield and composition of different fractions of EPS produced by microorganisms [45,46]. In our research, LB-and TB-EPS contained a large portion of proteins (PN/PS ratio = 1.0 -2.5, and 1.6 -3.6, respectively).…”
Section: Eps Production Composition and Assessment By 3d-eemmentioning
confidence: 62%
“…There have also been diverse opinions and results among researchers on the role of different EPS compositions, particularly PN and PS of EPS, in aerobic granulation. 50,51 According to Rusanowska et al (2019) and Oliveira et al (2020), the PN in EPS serves the function of enhancing microbial aggregation, maintaining the structural stability and protecting the biomass against environmental stress and dehydration. 46,52 Extracellular PS is vital in maintaining the strength and cell-tocell interaction of aerobic granules.…”
Section: Extracellular Polymeric Substancesmentioning
confidence: 99%